A 19-year-old woman with Irritable Bowel Syndrome with Constipation (IBS-C), Chronic Gastritis, Psychological Stress with Risk Factors of Unhealthy Diet, Vulnerable Economic Status, and Unhealthy Work Environment - Kuntadi, Muhammad; Trsinawati, Heksa (Jurnal Ilmu Kedokteran Keluarga, 2025)
Background: Irritable Bowel Syndrome with Constipation (IBS-C), chronic gastritis, and insomnia are functional disorders frequentlyinfluenced by psychosocial stressors and unhealthy lifestyle. Case Presentation: A 19-year-old woman presented with left abdominal painpersisting since March 2025, worsening in the last four days, associated with constipation, nausea, and reduced oral intake. She alsoreported insomnia for the past four months, triggered by work-related stress and financial difficulties. Physical examination revealednormal findings except for tachycardia. Supporting examinations included IBS Symptom Severity Score 240 (moderate IBS), SRQ-20score 9/20 (suggestive of psychological distress), and Insomnia Severity Index 19 (moderate insomnia). Discussion: The patient wasdiagnosed with IBS-C, chronic gastritis, and psychological stress with insomnia. The interplay between gastrointestinal symptoms andpsychological stress highlights the biopsychosocial approach in family medicine. Non-pharmacological interventions such as dietmodification, sleep hygiene, and stress management were prioritized, complemented with pharmacological agents (hyoscine butylbromide,antacids, lactulose, PPI). Conclusion: Holistic management addressing biomedical, psychological, and social aspects is crucial inimproving outcomes in young patients with IBS-C, chronic gastritis, and insomnia